On the Recollection of Campanula wattiana Nayar and Babu from Uttar Pradesh, India - Maiti, Gaurgopal (Indian Forester, 1986)
Campanula wottiona Nayar and Babu is described in 1970 based on the old collections from Jammu&Kashmir, Uttar Pradesh and Himachal Pradesh during 1864-1900. After a lapse of about 75 years this plant has again been collected from one of the type localities of Uttar Pradesh.